(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
The liquid chromatography mass spectrometry (LC-MS) compatible, stability-indicating, specific, linear, accurate, sensitive with less run-time related impurities reversed phase high-performance liquid chromatography (RP-HPLC) related impurities method has been developed for olmesartan medoxomil (OLM), chlorthalidone (CHLR), and cilnidipine (CIL) drug combinations, and the method has been validated according to ICH and US-FDA guidelines. The chromatographic separation was performed by using Hypersil-BDS Thermo-Scientific, C18 (12.5 cm, 4.6 mm, 5 microns particle size) column. Mobile phase-A was prepared by mixing 3.85 gm ammonium acetate in HPLC water and adjust pH 5.0 by using diluted acetic acid. Acetonitrile was taken as mobile phase-B. Initial mobile phase ratio (55:45 v/v) was adjusted for mobile phase-A: mobile phase-B followed by gradient program. Other chromatographic conditions such as column temperature 25 degrees, flow rate 1.0 mL/minutes with the detection wavelength at 260 nm. The retention time for CHLR impurity A, olmesartan (OL), OLM impurity A, were found about 2.7, 3.3, and 7.2 minutes respectively, with a total run time of 18.0 minutes. The linearity calibration plot was performed and found linear relationship over the concentration range of 1.25 limit of quantitation (LoQ)–18.75 μg/mL, 3.6 LoQ–60.0 μg/mL, 3.6 LoQ–60.0 μg/mL respectively for CHLR impurity A, OL and OLM impurity A respectively. The limit of detection (LoD) and LoQ were found 0.4 ppm (μg/mL) and 1.2 ppm (μg/mL), 1.2 ppm (μg/mL) and 3.5 ppm (μg/mL), 1.1 ppm (μg/mL) and 3.3 ppm (μg/mL) for CHLR impurity A, OL and OLM impurity A respectively. The accuracy was determined by recovery studies and was found between 90.0–110.0%. The developed analytical method has been validated for LoD-LoQ, specificity, linearity, accuracy, precision, robustness, and ruggedness, which were well within the acceptance limit as per ICH guidelines. All the degradation products generated by stress conditions were found to be well separated from one another (all drug components and impurities). The developed method with shorter runtime was successfully implemented for routine quality control and stability analysis to check the quality of OLM, CHLR, and CIL drug combinations.